Investment directions and principles of entrepreneurial activity development in the regions - A.B., KURBANOV; N.M., JALILOVA (The journal of contemporary issues in business and government, 2021)
The evolutionary development trends of small business and private entrepreneurship has been examined in this article. The directions of theoretical analysis of scientists on the category of entrepreneurship are indicated. Assessment of the conditions created for entrepreneurship and indicators of organizational and economic development are analyzed. The mechanism of ensuring economic and financial balance of entrepreneurship in the regions and regions has been studied. The role of business entities and their activities in investment policy is also studied. The directions of solving the existing problems in the field of entrepreneurship through direct and foreign investments are indicated. The principles are proposed on the basis of investment directions for entrepreneurship.